Vegetarian, gluten-free, and energy restricted diets in female athletes - Cialdella-Kam, L.; Kulpins, D.; Manore, M. M. (Sports, 2016)
Female athletes who follow a diet that fails to meet energy and nutrient needs are at risk for musculoskeletal injuries, menstrual disturbances, and poor sports performance. Common nutritional concerns for the female athlete include low energy availability (EA) (i.e., energy intake from food remaining for metabolic processes after accounting for energy expended during exercise) and inadequate dietary intakes (i.e., not meeting sports nutrition guidelines) of carbohydrates, protein, essential fatty acids (EFAs), B-vitamins, calcium, iron, and vitamin D. Low EA and the associated nutrient deficiencies are more common in athletes who compete in weight-sensitive sports (i.e., aesthetic, gravitational, and weight category sports) because low body fat and mass confer a competitive advantage. Other athletes at risk for energy and nutrient deficits include athletes following a vegetarian or gluten-free diet (GFD). Careful dietary planning can help an athlete meet energy and nutrient needs. This review covers the nutrition issues associated with low EA and special diets (i.e., vegetarian and GFD) and describes strategies to help female athletes meet their energy and nutrient needs